Administrations of autochthonous probiotics altered juvenile rainbow trout Oncorhynchus mykiss health status, growth performance and resistance to Lactococcus garvieae, an experimental infection. Issue 86 (March 2019) - Mohammadian, Takavar; Nasirpour, Mahdieh; Tabandeh, Mohammad Reza; Heidary, Amir Ali; Ghanei-Motlagh, Reza; Hosseini, Seyed Samad
Abstract: The present study was tested how Oncorhynchus mykiss can respond to dietary supplementations of autochthonous probiotics, including Lactobacillus delbrukei subsp. bulgaricus and Lactobacillus acidophilus and Citrobacter farmeri by measuring different parameters. To address that, 300 fish weighing 19.08–32.9 g were fed by probiotics-enriched diets, containing 5 × 10 7 CFU g −1 for 60 days. Our results indicated that probiotics, especially L. acidophilus and L. bulgaricus are involved in enhancing the growth performance of this species as compared with the control group. Blood profile (Hemoglobin and Hematocrit) showed significant (P < 0.05) increases in probiotic fed groups compared with the control. Serum lysozyme and complement activities were higher in probiotic-fed fish while similar changes were not observed in the case of bactericidal activity and Nitroblue Tetrazolium (NBT) reduction. Better colonization of lactic acid bacteria in fish intestine was observed following L. acidophilus and L. bulgaricus administrations (P < 0.001). Digestive enzyme activities of intestine, including amylase, trypsin, lipase and alkaline phosphatase were elevated either significant or insignificant while protease activity did not act the same. All probiotic treatments led to mild or strong (P < 0.001) up-regulation of cytokine and growth gene expressions of intestine in comparison with the control group. Higher in vitro antagonist activities of L. acidophilus and L. bulgaricus against the Lactococcus garvieae were coincident with in vivo challenge test. The relative percentage of survival (RPS) was obtained 63.71 and 51.56 for L. bulgaricus and L. acidophilus, respectively, which were higher in those treated fish as compared to control fish. Our results may suggest that the probiotics, applied here, can promote growth performance by improving digestive enzyme activity, gut micro flora and growth gene expression. Up-regulation of immune regulatory proteins may increase the non-specific immune responses and bacterial resistance in this species as well. Highlights: Fish responses or even adjustment to different autochthonous probiotics might be different from molecular to organism. L. acidophilus and L. bulgaricus can promote growth performance by improving digestive enzyme activity, gut micro flora. Up-regulation of immune regulatory proteins may increase the non-specific immune responses and bacterial resistance.